Youth Policy Adaptation in the Spanish Rural Context: A Case of Study of Youth Policy Programs - Querol, Vicent A.; Gómez Nicolau, Emma; Sanchez, Xavier Ginés (Calitatea Vieții, 2021)
This article aims to describe a series of policies concerning Spanish youth and their degree of adaptation to Spanish rural areas in terms of the key elements of social dynamics in Spain’s rural areas. It considers some of the general youth policies being implemented, and identifies those which appear to be closer to these specific territories. After discussing these policies, it is clear that, on the one hand, there is a lack of flexibility and adaptation to the particular circumstances of rural areas. However, on the other hand, it is also possible to cautiously point out some policies which do indeed propose more appropriate actions for rural areas, as well as observe pilot experiences and partnerships between NGOs and the administration that not only have some outstanding elements, but also the potential to stretch into the future